RUANG PUBLIK SEBAGAI TEMPAT WISATA KAUM MILENIAL KOTA AMBON - AUGUST JOHANNES RICOLAT UFIE , (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
An attractive and adequate public space is an attraction for millennials. This research was an aim to find a variety of public spaces in Ambon City, the visits and activities carried out, ending with criticism and expectations about public space. This research is survey research. The results showed a variety of public spaces included parks, fields, monuments, beach open spaces, and landmarks. A triggered visits by visual attractiveness, scheduled activities, availability of infrastructure and facilities, ease of access, distance, motive, and openness. The activities carried out are enjoying the scenery, taking pictures, and resting. The criticism was due to the inadequate management and accompanied by hopes that greening along the roads would be implemented and add other public spaces.